Correlation between circulating fibrosis biomarkers with left atrial function and left atrial volume index in rheumatic mitral stenosis - Asrial, An A.; Reviono, Reviono; Soetrisno, Soetrisno; Setianto, Budi Y.; Widyaningsih, Vitri; Nurwati, Ida; Wasita, Brian; Pudjiastuti, Anggit (Narra J, 2024)
Mitral stenosis is the most common rheumatic heart disease (RHD) disorder worldwide, including in Indonesia. This pathological condition causes left atrial pressure, leading to left atrial fibrosis that affects the structure and function of the left atrial as well as the clinical condition. The aim of this study was to assess the correlation between circulating fibrosis biomarkers with net atrioventricular compliance (Cn) as a parameter of left atrial function, and left atrial volume index (LAVI) as a parameter left atrium structure of changes. A cross-sectional study was conducted at Panti Rahayu Hospital and Permata Bunda Hospital, Purwodadi, Central Java, with a total of 40 RHD patients with severe mitral stenosis. The ELISA was used to measure the levels of carboxy-terminal propeptide of type I procollagen (PICP), matrix metalloproteinase I (MMP-1), tissue inhibitor matrix metalloproteinase 1 (TIMP-1), and transforming growth factor-β1 (TGF-β1). The left atrial function was assessed by measuring Cn, and the LAVI parameters were measured to assess left atrium structure/size. The mean levels of circulating fibrosis biomarkers were as follows: PICP 153.96±89.12 ng/mL; MMP-1 1.44±2.12 ng/mL; MMP-1/TIMP-1 ratio 0.38±0.54 and TGF-β1 2.66±1.96 pg/mL. From the echocardiographic evaluation, the mean Cn was 5.24±1.93 mL/mmHg and the mean LAVI was 152.55±79.36 mL/m2. There were significant correlation between MMP-1 and MMP-1/TIMP-1 ratio with Cn (r=0.345 and r=0.333, respectively; both had p<0.05). PICP and TGF-β1 biomarkers did not significantly correlate with Cn (p>0.05). Meanwhile, none of the biomarkers had a significant correlation with LAVI (p>0.05). This study highlights that MMP-1 and MMP-1/TIMP-1 ratio are potentially to be used as markers to determine the Cn in RHD patients with severe mitral stenosis. However, further studies with a higher sample size are needed to confirm this finding.